Current status of the anterior middle superior alveolar anesthetic injection for periodontal procedures in the maxilla - Ahad, Abdul (J Dent Anesth Pain Med, 2019)
Periodontal procedures require adequate anesthesia not only to ensure the patient's comfort but also to enhance the operator's performance and minimize chair time. In the maxilla, anesthesia is often achieved using highly traumatic nerve blocks, apart from multiple local infiltrations through the buccal vestibule. In recent years, anterior middle superior alveolar (AMSA) field block has been claimed to be a less traumatic alternative to several of these conventional injections, and it has many other advantages. This critical review of the existing literature aimed to discuss the rationale, mechanism, effectiveness, extent, and duration of AMSA injections for periodontal surgical and non-surgical procedures in the maxilla. It also focused on future prospects, particularly in relation to computer-controlled local anesthetic delivery systems, which aim to achieve the goal of pain-free anesthesia. A literature search of different databases was performed to retrieve relevant articles related to AMSA injections. After analyzing the existing data, it can be concluded that this anesthetic technique may be used as a predictable method of effective palatal anesthesia with adequate duration for different periodontal procedures. It has additional advantages of being less traumatic, requiring lesser amounts of local anesthetics and vasoconstrictors, as well as achieving good hemostasis. However, its effect on the buccal periodontium appears highly unpredictable.